The iHV Emotional Wellbeing at Work Champions Programme: Building capacity to protect and enhance the emotional wellbeing of the health visiting workforce in the UK - Sharin Baldwin; Rachel Stephen; Patricia Kelly; Philippa Bishop (Elsevier, 2022)
The Institute of Health Visiting (iHV) Emotional Wellbeing at Work Programme was developed during the COVID-19 pandemic to support the health visiting services to deal with the increased demands placed on them. This paper discusses the development of the iHV Emotional Wellbeing at Work (EWW) Champions Programme, which has built on the original model to enable the creation of EWW Champions. The iHV has a good track record of building leadership and capacity for rolling out training and development on a wider scale using the iHV Champions model of training. The portfolio currently includes a range of Perinatal and Infant Mental Health Champions (Baldwin and Kelly, 2016; Baldwin et al., 2018) [1,2], Research Champions (Mugweni et al., 2019) [3], Delivering Different News Champions, Healthy Weight and Healthy Nutrition Champions, Changing Conversations: Autism Ambassadors, and Neonatal Families Ambassadors. This paper discusses how the EWW programme was further developed to create this Champions' model to enable other experienced and skilled health visitors to become EWW facilitators. Through this model, trained health visitors can support their colleagues in the workplace, protecting and enhancing their emotional wellbeing at work and broadening access to support services and resources.